The Protection of Women and Children as Victims of Human Trafficking in Jambi Province - Hafrida Hafrida; Nelli Herlina; Zulham Adamy (Jambe Law Journal, 2018)
The research aims at studying the policy of the Regional Government in protecting the victims of human trafficking, especially females and children. This legal research is based on an empirical study at Regional Police (POLDA), P2TP2A, and Social Services office in Jambi Province. The Law Number 35/2014 on the Amendment of The Law Number 23/2002 on Child Protection provides a greater portion for the Regional Government to take active roles in providing child protection and Presidential Regulation Number 69/2008 about Task Force Prevention and Handling the Criminal Act of Trafficking Victim. Using analysis of descriptive qualitative, it is learned that the handling of the women and children as victims of trafficking remain partially. The responsible institutions have not well-coordinated because a task force as commissioned by Presidential Regulation number 69/2008. The results show that Jambi Province has passed Jambi Province Regional Regulation Number 2/2015 on Prevention and Handling of Human Trafficking towards Females and Children. However, the study also shows that the regulation has not been applied by related parties since Governor’s regulation as implementing regulation is inexistent.